Technical Guidance of Science Teachers in The Preparation of Scientific Based Teacher Books, to Improve Teacher Professionalism in West Pasaman Regencys - Ratnawulan - Ratnawulan (Pelita Eksakta, 2020)
There are problems in implementing integrated science learning in SMP / MTs in West Pasaman Regency. Most teachers do not have a handbook according to the nature of integrated science. Existing teacher books, the fields of biology, chemistry and physics are still not integrated into a single unit. The next problem, the low motivation and creativity of teachers in finding sources of information and integrating fields of study for learning. The solution offered is to increase the professionalism of science teachers is through technical guidance for making science-based Integrated science teacher books. Integrated science learning is designed with integrative thematic learning that is learning that integrates a learning concept with another subject. This Bimtek succeeded in increasing the competence of science teachers in MGMP Pasaman Barat in developing Integrated Science teacher books with themes in accordance with local wisdom with the Scientific Approach.